Hydraulic Properties of Flow Over Different Types of Spillways: A Review - Bashar N.A.M.; Zainol M.R.R.M.A.; Aziz M.S.A.; Zawawi M.H.; Mazlan A.Z.A. (Springer Science and Business Media Deutschland GmbH, 2025)
A review of hydraulic properties of flow over the spillway via physical experiment and computational approaches is presented in this paper. The hydrodynamic analysis of flow via the computational fluid dynamics (CFD) approach is vital in solving complex flow problems where the field and experimental assessments are limited. The most selected and efficient turbulence model is the RNG k-? model. Free water surface profile, Froude number, flow regime, velocity, and pressure distribution were identified as the most studied parameters of flow over the spillway structure. These hydraulic characteristics of flow were affected by the geometrical configuration such as the type and arrangement of the spillway. The skimming flow was recognized as the most frequent type of flow in the actual field. The stepped and hybrid types were identified as the most studied concerning functionality in controlling the velocity and dealing with rapidly varied flow types as compared to the ogee-type. Understanding the hydraulic properties of flow is mandatory and important to ensure the serviceability of the spillway structure to safely transfer the water to the downstream section and to minimize the massive impacts of hydraulic jump together with the presence of air?water interface, cavitation, and downstream scour problem. The potential future research work includes an in-depth relationship between the hydraulic characteristic of flow between the efficient spillway structure and the baffle block structure in controlling the hydraulic jump in the stilling basin area. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.